The Interplay of Health, Pleasure and Wellness in British Seaside Resorts: the Case of Skegness on the Lincolnshire Coast - Mohamed Chamekh (Revue Française de Civilisation Britannique)
This article seeks to demonstrate the vitality of the health dimension in the growth of Skegness as a seaside resort. It shows the way changes in the medical profession, especially the use of seawaters for the treatment of diseases, contributed to the growth of seaside resorts in Britain. It highlights the way the health culture interacted with the principle of pleasure to contribute to the growth of seaside resorts. This paper also seeks to explore the potential role the National Health Service (NHS) could play in the transformation of Skegness into a wellness destination especially with the NHS emphasis on wellness as a new strategy to prevent and manage health problems, the constant inflow of an elderly generation into the resort, and an ageing population whose health needs are changing.